Nighttime sleep duration and hedonic eating in childhood - McDonald, L (Int J Obes (Lond), 2015)
BACKGROUND: Higher food intake is implicated in the elevated risk of obesity associated with shorter sleep in children, but the mechanisms driving higher intake are uncertain. Research in adults suggests that acute sleep deprivation affects brain reward systems, which increases responsiveness to palatable foods. However, there have been few studies addressing habitual sleep duration, and few in children, among whom the strongest associations with body mass index (BMI) are seen. OBJECTIVE: The objective of this study is to test the hypothesis that shorter-sleeping children are more food responsive and explore the mediation of the relationship between sleep and weight by food responsiveness (FR). METHODS: Participants were families from Gemini, a UK twin birth cohort, who had provided complete information on their children's sleep and appetite at age 5 years (n=1008). One child from each twin pair was randomly selected for analyses. Nighttime sleep duration was calculated from parent-reported bedtime and wake time, and categorised as shorter, adequate or longer according to age-specific reference values. FR was assessed with the Child Eating Behaviour Questionnaire. BMI s.d. scores (BMI-SDS) were calculated from parent-measured heights and weights using the UK 1990 reference data and were available for 494 children. RESULTS: There was a significant linear association between shorter sleep and higher FR at age 5 years (P for linear trend=0.032), which was maintained after adjusting for age, sex, birth weight, maternal education and BMI-SDS. In the subset with BMI data at age 5 years, shorter sleep was associated with higher BMI-SDS (P=0.026) as expected. Testing for mediation by adding FR to the model attenuated the linear relationship to borderline significance (P=0.049), suggesting partial mediation. CONCLUSIONS: Shorter sleep in childhood is associated with higher FR, which may partly explain the association between shorter sleep and adiposity in childhood.